God's jury : the Inquisition and the making of the modern world - Murphy, Cullen (Houghton Mifflin Harcourt, 2012)
The acclaimed author of "Are We Rome?" brings his highly praised blend of deep research, colorful travelogue, and insightful political analysis to a new history of the Inquisition. Exploring the Inquisition from its establishment in 1231 onwards, Murphy argues that not only did its offices survive into the twentieth century, its spirit lingers on in the modern world too.